2022
DOI: 10.1002/aenm.202200569
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Suppression of Oxygen Release by LiNi0.8Co0.1Mn0.1O2 Cathode under Overcharge Conditions

Abstract: The safety issue of lithium‐ion batteries is a crucial factor limiting their large‐scale application. Therefore, it is of practical significance to evaluate the impact of their overcharge behavior because of the severe levels of oxygen release of cathode materials during this process. Herein, by combining a variety of in situ techniques of spectroscopy and electron microscopy, this work studies the structural degradation of LiNi0.8Co0.1Mn0.1O2 (NCM811) accompanying the oxygen release in the overcharge process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 56 publications
(90 reference statements)
0
33
0
Order By: Relevance
“…With the development of electric vehicles and portable electronic devices, there is a growing demand for lithium-ion batteries (LIBs), especially for those with high specific energy, fast charging capability, and high safety. Although the current collector, as an electrochemically inactive component, does not contribute to the energy of the battery, it is an indispensable component and has an important impact on the overall electrochemical performance and reliability of LIBs. , Nowadays, the commonly used current collectors of LIBs are aluminum (Al) foil and copper (Cu) foil due to their nearly irreplaceable economic applicability. However, for the consideration of mobile portability, the obvious drawback of these metallic materials is huge weight, accounting for about 15 and 50% of the total mass of cathode and anode, respectively, , resulting in a huge loss of specific energy of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of electric vehicles and portable electronic devices, there is a growing demand for lithium-ion batteries (LIBs), especially for those with high specific energy, fast charging capability, and high safety. Although the current collector, as an electrochemically inactive component, does not contribute to the energy of the battery, it is an indispensable component and has an important impact on the overall electrochemical performance and reliability of LIBs. , Nowadays, the commonly used current collectors of LIBs are aluminum (Al) foil and copper (Cu) foil due to their nearly irreplaceable economic applicability. However, for the consideration of mobile portability, the obvious drawback of these metallic materials is huge weight, accounting for about 15 and 50% of the total mass of cathode and anode, respectively, , resulting in a huge loss of specific energy of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al illustrated that at a charging cutoff voltage of 4.8 V, oxygen release from Ni-rich NCM ternary cathode materials also occurred. Sun et al also observed oxygen release from NCM811 at a charging cutoff voltage of 4.7 V. Meanwhile, it was also demonstrated that the damage of the crystal structure became more severe at elevated temperatures …”
Section: Introductionmentioning
confidence: 95%
“…Zhang et al 38 illustrated that at a charging cutoff voltage of 4.8 V, oxygen release from Ni-rich NCM ternary cathode materials also occurred. Sun et al 39 also observed oxygen release from NCM811 at a charging cutoff voltage of 4.7 V. Meanwhile, it was also demonstrated that the damage of the crystal structure became more severe at elevated temperatures. 40 We demonstrated previously that the cation mixing of Li + / Ni 2+ occurring in the NCM811 cathode during long-term cycling affected severely its heat generation power.…”
Section: Introductionmentioning
confidence: 96%
“…These disadvantages will deteriorate the interfacial contact among primary particles and aggravate interface side reactions, thereby resulting in the increasing of polarization resistance and irreversible capacity. Additionally, the energy band of the 2p electron orbitals of O 2– is partially overlapping with the e g electron orbitals of Ni 3+/4+ , which renders them taking part in charge compensation with the generation of abundant Ni 4+ when charged above 4.1 V. , This circumstance is accompanied by the formation of oxygen-free radicals and O 2 . They will further react with the organic electrolyte, causing severe thermal runaway behavior. , …”
Section: Introductionmentioning
confidence: 99%